Analisis Burnout Dokter IGD terhadap Kualitas Pelayanan dan Kepuasan Pasien dalam Perspektif Service Profit Chain - Orienza Sativa Novitaloka; Puspa Widiyawati; Ria Anggraeni Lubis; A Rohendi (Institut Nalanda, 2026)
The Emergency Department (ED) is a hospital unit characterized by high work pressure, which may lead to physician burnout. This condition not only affects healthcare workers but also has implications for service quality and patient satisfaction. This study aims to analyze the experiences of burnout among ED physicians and its impact on service quality and patient satisfaction from the perspective of the Service Profit Chain. This research employs a qualitative approach with a phenomenological design. The informants consisted of 7 participants, including 4 ED physicians as primary informants and 3 patients or their family members as supporting informants, selected purposively. Data were collected through in-depth interviews, observations, and documentation, and analyzed using the interactive model of Miles and Huberman. The findings indicate that burnout is characterized by emotional exhaustion, which affects service behavior, particularly in communication, empathy, and responsiveness. Although professionalism is maintained, there is a decline in the quality-of-service interaction, which influences patients’ experiences and satisfaction. This study demonstrates that burnout indirectly affects patient satisfaction through the quality-of-service interaction as the main mechanism. From the Service Profit Chain perspective, the internal condition of healthcare workers is a strategic factor in improving service quality and patient satisfaction.